Developing a Structural Model for Predicting Body Dysmorphic Disorder Based on Anxiety Sensitivity with the Mediating Role of Fear of Negative Evaluation in Women with a Body Mass Index of 30 or Higher - Kharrazi, Mona; Dokanehi Fard, Farideh; Khasmohammadi, Mahdi (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to develop and test a structural model predicting the level of body dysmorphic disorder (BDD) based on anxiety sensitivity, with the mediating role of fear of negative evaluation among women with a body mass index (BMI) of 30 or higher. Methods and Materials: The study employed an applied, quantitative, and descriptive–correlational design using a structural equation modeling (SEM) approach. The statistical population comprised women with a BMI ≥ 30 who attended diet therapy centers and health houses in Tehran during 2023–2025. Using multi-stage cluster and convenience sampling, 391 respondents were selected. Data were collected through three standardized instruments: the Modified Yale–Brown Obsessive–Compulsive Scale for Body Dysmorphic Disorder (Goodman et al., 2017), the Anxiety Sensitivity Index (Floyd et al., 2005), and the Brief Fear of Negative Evaluation Scale (Leary, 1983). Data analysis was performed using SPSS version 27 and SmartPLS version 3.3, with validity confirmed through content and construct measures and reliability through Cronbach’s alpha, composite reliability, and McDonald’s omega. Findings: The results indicated that anxiety sensitivity had both direct and indirect effects on body dysmorphic disorder, with fear of negative evaluation serving as a significant mediator. The standardized total path coefficient (β = 0.867) revealed that anxiety sensitivity strongly predicted BDD severity through this mediating mechanism. All path coefficients were statistically significant at the 0.01 level (t > 2.58), confirming the hypothesized relationships. The model demonstrated acceptable fit indices, supporting its structural validity. Conclusion: Anxiety sensitivity and fear of negative evaluation play crucial and interconnected roles in explaining the development and maintenance of body dysmorphic disorder among women with obesity.